2005
DOI: 10.1002/ejoc.200500010
|View full text |Cite
|
Sign up to set email alerts
|

Tautomeric Self‐Dimerization and Molecular Recognition Properties of2‐Aminopyrimidinone Derivatives as Triple Hydrogen‐Bonding Modules in Molecular Assemblies

Abstract: A triple hydrogen-bonding module based on 6-alkynyl-2-amino-3H-pyrimidin-4-one was developed such as for selfdimerization and for nucleobase recognition processes. The strength of the module for the self-dimerization was determined by NMR and fluorimetric analyses in chloroform (ΔG 298 = -22 to -23 kJ/mol). DFT calculations and X-ray structure analysis showed that the self-dimerization consists of the three-point hydrogen-bonding including two kinds of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…(14) Heterocyclic ring systems were shown to readily participate in Sonogashira-type couplings [175,306]. Some more complex examples include reaction of 5-iodoarabinosyluridine [307], 3-iodofuran [308], 6-chloro-9H-purine [309], 8-bromoadenosine [310], 2,6-bis(4-iodopyrazol-1-yl)pyridine [311], 6-chloro-3H-pyrimidin-4-one [312], bromo-oxabicyclo[3.2.1]octadienes [28], a triazolopyrazinyl bromide [172], 5-trifloxyindoles [29], 5-bromobenzofuran [183], 3-iodo-5-bromoindole and 3-iodo-5-bromo-3-indazole [182], 7-bromo-pyrido [2,3-b]pyrazine [185], 5-iodo-1,2,3-triazoles [186,313], 4,5-diiodoimidazole [314] and 4-iodo-2-bromoquinoline [315] derivatives. Sonogashira coupling of 2-iodophenols followed by cyclization to give benzofurans was reported [183].…”
Section: Carbon-carbon Bond-forming Reactions Using Terminal Alkynes mentioning
confidence: 99%
“…(14) Heterocyclic ring systems were shown to readily participate in Sonogashira-type couplings [175,306]. Some more complex examples include reaction of 5-iodoarabinosyluridine [307], 3-iodofuran [308], 6-chloro-9H-purine [309], 8-bromoadenosine [310], 2,6-bis(4-iodopyrazol-1-yl)pyridine [311], 6-chloro-3H-pyrimidin-4-one [312], bromo-oxabicyclo[3.2.1]octadienes [28], a triazolopyrazinyl bromide [172], 5-trifloxyindoles [29], 5-bromobenzofuran [183], 3-iodo-5-bromoindole and 3-iodo-5-bromo-3-indazole [182], 7-bromo-pyrido [2,3-b]pyrazine [185], 5-iodo-1,2,3-triazoles [186,313], 4,5-diiodoimidazole [314] and 4-iodo-2-bromoquinoline [315] derivatives. Sonogashira coupling of 2-iodophenols followed by cyclization to give benzofurans was reported [183].…”
Section: Carbon-carbon Bond-forming Reactions Using Terminal Alkynes mentioning
confidence: 99%
“…For simple dimerizations by tautoleptic aggregation, association constants of isocytosine compounds in CHCl 3 are approximately 10 4 m À1 . [11] However, it is obvious that the formation of the cyclic aggregate of 2 has an association constant that is at least one order of magnitude higher based on dilution titrations and on a competition experiment ( Figure S42 in the Supporting Information). The aggregation of planar monomers to defined two-dimensional cyclic structures by induced tautomerization has also been observed, [23,24] but such monomers are not able to display topological diversity as enantiomerically pure monomers.…”
mentioning
confidence: 98%
“…[6][7][8][9][10][11] Accordingly, we have designed a monomer 1 containing one isocytosine unit at each end of an enantiomerically pure C 2 -symmetric angle bar, the bicyclo-[3.3.1]nonane system ( Figure 1, bottom left). Molecular modeling at the semi-empirical level (see the Supporting Information) indicated that a cyclic tetramer 1 4 is favored and that its quadratic cavity would have a width of approximately 13 from face to face in hetero-and homotautoleptic aggregation ( Figure 3).…”
mentioning
confidence: 99%
“…Recently, two sets of nonnatural H-bonding base pairs were introduced into a DNA duplex, resulting in an all-pyrimidine or all-purine genetic system. Inouye and co-workers have reported synthesis and utilization of artificial nucleobases [136], and developed a new synthetic route for alkynyl C-2-deoxy-b-dribofuranosides, which leads to easy introduction of the nonnatural bases and other aromatics into phosphodiester-based DNA-like skeletons [137]. Indeed, various fluorophores such as pyrene, perylene, and anthracene could be attached to the deoxyribose through the acetylenic bonds in high yields.…”
Section: Size-expanded Artificial Dnas With Nonnatural H-bonding Basementioning
confidence: 99%